The storm before the calm : America's discord, the coming crisis of the 2020s, and the triumph beyond - Friedman, George (Doubleday, 2020)
"The master geopolitical forecaster and New York Times bestselling author of The Next 100 Years focuses on the United States, predicting how the 2020s will bring dramatic upheaval and reshaping of American government, foreign policy, economics, and culture"--